Identifikasi Faktor Faktor Yang Mempengaruhi Kesenjangan Gender Dalam Akses Dan Partisipasi Pendidikan Tinggi Di Indonesia - Patricia Swalika Irawan; Fikri Dwi Agustian; Dwi Putri Lestarikan (CV. ITTC INDONESIA, 2024)
This research explores the social, economic and cultural factors that play a role in creating gender disparities in access to and participation in higher education in Indonesia, and how government policies can help overcome these inequalities. This research uses a normative legal research method with a conceptual and statutory ap-proach. The analysis focuses on existing laws and policies, as well as various legal concepts and concepts related to gender equality and education rights. The data used consists of primatice, secondary, and tertiary legal materials obtained through literature study. The results show that the gender gap in higher education is still influenced by the norm of traditional cultural and social norms, family economic constraints, and limited educational infrastructure in remote areas. Although there have been various government policies, their effectiveness is still limited since those policies have not fully considered the barriers faced by women at the grassroots level. Thus, a more comprehensive approach is needed, including raising public awareness, providing more targeted financial support, and social change that supports gender in equality so that women have equal access to higher education.